Flexible loop closing control method for an active distribution network based on dual rotary phase shifting transformers. Issue 20 (27th August 2022) - Yan, Xiangwu; Peng, Weifeng; Wang, Yang; Aslam, Waseem; Shao, Chen; Li, Tiecheng
Abstract: Load transfer without power interruption in the loop closing of an active distribution network is the core technology for improving the reliability of power supply. A single rotary phase shifting transformer (RPST) is used in the loop closing scenario with a 30° phase angle difference. However, its regulation mode is single and cannot realize flexible loop closing under any voltage deviation. In this study, a dual rotary phase shifting transformer (DRPST) is proposed to achieve the function of continuously regulating voltage amplitude and phase angle at the loop closing point through the cooperation of dual rotor angles. This DRPST exhibits the advantages of a flexible control mode, high control precision, and high reliability. First, the working principle and mathematical model of the proposed DRPST are analyzed in accordance with its topology. Second, the voltage phase difference feedback method at both sides of the loop closing point based on virtual power is adopted, and the reference value of the DRPST synthesis vector of voltage is obtained by combining with voltage phase and amplitude deviations. Then, the reference value is converted and decomposed into the reference values for dual rotary phase shifting angles, realizing the non‐differential regulation of voltage at both sides of the loop closing point through the closed loop control of double rotor angles and the coordinated control of the servo motors' speed. Finally, a DRPST device with a capacity of 40 kVA is developed and a loop closing experiment is performed, verifying the feasibility and effectiveness of the proposed DRPST in realizing the loop closing of an active distribution network.